A qualitative evaluation of professionals' experiences of conducting Beardslee's family intervention in families with parental psychosis. Issue 5 (20th October 2017) - Strand, Jennifer; Rudolfsson, Lisa
Abstract: After Sweden passed new health care legislation in 2010, Beardslee's preventive family intervention (FI) was implemented to meet children's rights to information and support. No studies have yet evaluated perceived effectiveness of FI in families with parental psychosis or its reception by families or professionals. This study focused on professionals' experiences of offering FI to parents with psychosis, their partners, and their children. We conducted 11 semi-structured interviews with FI-educated professionals at open care psychosis service units. Both authors applied thematic analysis to the interview data. The main reported benefit of FI was more open communication in the family; discussing the parent's illness was thought to be helpful for all family members. Psychoeducation was described as particularly useful because family members generally seemed to lack sufficient information about psychosis. The FI manual also made professionals more confident about asking about patients' parenting capacity and their children's wellbeing. Despite positive descriptions, participants had conducted few FI interventions because of heavy workloads, organizational problems, and patients' resistance to talking about their children. These barriers need to be addressed because children of parents with psychosis are a vulnerable group in great need of information and support.